Multivariate and geostatistical approaches in assessment of groundwaterquality for drinking purpose in shallow wells(of Amol-Babol Plain, Iran) - Narany, Tahoora Sheikhy; Ramli, Mohammad Firuz; Aris, Ahmad Zaharin; Sulaiman, Wan Nor Azmin; Fakharian, Kazem (2012)
The knowledge of groundwater quality as a primary resource of potable uses is significant in the arid and semi-arid area of the world such as Iran. Groundwater quality evaluation is undertaken to determine the suitability of the water for drinking uses. In the Amol- Babol Plain, many shallow wells have been constructed for agriculture, and domestic usages. The quality of these wells could be easily compromised by surface activities and runoff such as agricultural, residential and industrial activities. Groundwater samples were collected from 60 wells during the dry season in the 2009. Multivariate statistical analysis showed that Na+, Cl-, TDS, total coliforms, fecal coliforms, HCO3 -, BOD, COD and Ca2+ are significant parameters, which influenced groundwater quality for drinking purpose. The spatial distribution maps of the main pollutants were generated by using geostatistical tools. GIS software was used for the application of kriging method with cross-validation leading to the estimation of groundwater quality in the study area. Based on the analysis results and comparison with drinking water quality standard such as WHO and EPA, most of the study area falls in the moderately polluted zone. The results revealed that the groundwater in the north- east and east side of Amol-Babol Plain was unsuitable for drinking purpose, due to influence of anthropogenic contamination and salinization.